2012
DOI: 10.2341/10-355-l
|View full text |Cite
|
Sign up to set email alerts
|

Loading Standardization of Postendodontic Restorations In Vitro: Impact of Restorative Stage, Static Loading, and Dynamic Loading

Abstract: SUMMARY Objective The load capability of post-restored endodontically treated teeth (ETT) can be determined at different restorative stages. It was the aim of this study to compare the load capability of ETT at these stages. Materials and Methods Maxillary central incisors were divided into 4 groups (n=10) and endodontically treated. Specimens were restored with: (I) only glass fiber posts (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
2
10
0
2
Order By: Relevance
“…6 However, their subsequent study reported that dynamic loading prior to load-to-fracture testing of the complete restorative complex significantly decreased maximum load capability inconsequently. 1 Similar results were reported that when fiber posts–cores complex were subjected to cyclic loading, decreases in microtensile bond strength were observed. 7 …”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…6 However, their subsequent study reported that dynamic loading prior to load-to-fracture testing of the complete restorative complex significantly decreased maximum load capability inconsequently. 1 Similar results were reported that when fiber posts–cores complex were subjected to cyclic loading, decreases in microtensile bond strength were observed. 7 …”
Section: Introductionsupporting
confidence: 83%
“…The frequency of cyclic loading at 6 Hz in this study situated between 2 and 8 Hz and the 45° oblique loading in static test have been already applied by many researchers. 1,7,9,10 Such study approach is internationally well acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of in vitro studies performed to date have only evaluated the maximum load capability of tooth specimens, and extrapolating the observations made during destructive testing to clinical conclusions is not realistic. Artificial ageing is known to have a considerable impact on the data generated in load-to-fracture tests [36]. For this reason, an experimental design combining cyclic loading within physiological limits and simultaneous thermocycling was used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…3 The null hypothesis of this experiment was that neither the presence of fiber post nor residual coronal walls would affect the fracture resistance of premolars.…”
Section: Introductionmentioning
confidence: 96%